Implementasi Metode Eksperimen dalam Pembelajaran IPA Tentang Sumber Energi Alternatif pada Siswa Kelas IV MI Attaqwa Sawangan Depok - Chaira Saidah; Ernawati; Dede Hermawan; Asep Sujana; Umiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to increase interest in science lessons, especially material about alternative energy sources among class IV students at MI At Taqwa Sawangan Depok in the even semester of the 2023/2024 academic year. The data collection method uses the library research method. The data collection technique used is by listing all the variables that need to be studied, namely: learning implementation, experimental methods, alternative energy source materials. Select the necessary descriptive materials from available sources such as books, articles or biographies that are relevant to the problem being studied. This research can be concluded that the application of experimental methods in science learning can increase students' interest in learning and students' science learning outcomes, especially material on alternative energy sources.